2021
DOI: 10.3390/molecules26113203
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Potential of Aged Garlic Extract (AGE) and Its Active Constituent, S-allyl-l-cysteine, in Presence of Carvedilol during Isoproterenol-Induced Myocardial Disturbance and Metabolic Derangements in Rats

Abstract: This study was conducted to determine the potential interaction of aged garlic extract (AGE) with carvedilol (CAR), as well as to investigate the role of S-allyl-l-cysteine (SAC), an active constituent of AGE, in rats with isoproterenol (ISO)-induced myocardial dysfunction. At the end of three weeks of treatment with AGE (2 and 5 mL/kg) or SAC (13.1 and 32.76 mg/kg), either alone or along with CAR (10 mg/kg) in the respective groups of animals, ISO was administered subcutaneously to induce myocardial damage. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…We also reported that garlic, aged garlic extract and s-allyl cysteine showed antioxidant and hypolipidemic effects that were influenced by the administration of conventional antihypertensives ( Asdaq et al, 2009b ; Asdaq, 2015 ). Recently, we reported the interaction of aged garlic extract and its constituent s-allyl csyteine on isoprenaline induced myocardial infarction in rats ( Asdaq et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also reported that garlic, aged garlic extract and s-allyl cysteine showed antioxidant and hypolipidemic effects that were influenced by the administration of conventional antihypertensives ( Asdaq et al, 2009b ; Asdaq, 2015 ). Recently, we reported the interaction of aged garlic extract and its constituent s-allyl csyteine on isoprenaline induced myocardial infarction in rats ( Asdaq et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rats were injected with ISO (150 mg kg āˆ’1 , SC) twice at a 24 h interval. 23,24 Then one week later, rats received 1 ml of vehicle orally for six weeks.…”
Section: Experimental Designmentioning
confidence: 99%
“…Treatment with allicin has been shown to reduce hyperglycemia, polyuria, and NAG excretion. This is mainly attributed to the antioxidant properties of allicin [ 32 ].…”
Section: Medicinal Plants and Diabetic Nephropathymentioning
confidence: 99%